2016
DOI: 10.1002/eap.1366
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers reveal sea turtles remained in oiled areas following the Deepwater Horizon oil spill

Abstract: Assessments of large-scale disasters, such as the Deepwater Horizon oil spill, are problematic because while measurements of post-disturbance conditions are common, measurements of pre-disturbance baselines are only rarely available. Without adequate observations of pre-disaster organismal and environmental conditions, it is impossible to assess the impact of such catastrophes on animal populations and ecological communities. Here, we use long-term biological tissue records to provide pre-disaster data for a v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 52 publications
(62 reference statements)
0
21
1
Order By: Relevance
“…Our results differ from those of Vander Zanden et al (2016), who found no δ 13 C change in the scutes of loggerhead turtles that foraged in the oiled area after the spill; δ 13 C in the loggerheads was ca. -15 to -18 ‰ before and after the spill, which is similar to our pre-spill values for Lk (Fig.…”
Section: Incorporaion Of Oil Ccontrasting
confidence: 99%
See 3 more Smart Citations
“…Our results differ from those of Vander Zanden et al (2016), who found no δ 13 C change in the scutes of loggerhead turtles that foraged in the oiled area after the spill; δ 13 C in the loggerheads was ca. -15 to -18 ‰ before and after the spill, which is similar to our pre-spill values for Lk (Fig.…”
Section: Incorporaion Of Oil Ccontrasting
confidence: 99%
“…Other studies that have documented the incorporation of oil C into lower trophic levels and at different depths in the GoM also reported depleted C signatures (Graham et al 2010, Mitra et al 2012. In contrast to findings for loggerhead turtles (Vander Zanden et al 2016), our results indicate that the oil signature was transferred to Lk, as also reported for 2 species of mesopelagic GoM fishes (Quintana-Rizzo et al 2015). In the fish, a δ 13 C decrease in muscle samples collected 5 mo after the spill relative to pre-spill samples was attributed to the ingestion of oilcontaminated prey (Quintana-Rizzo et al 2015).…”
mentioning
confidence: 77%
See 2 more Smart Citations
“…Turtles tend to ex hibit high fidelity to oceanic and/or coastal foraging habitats (Goodman Hall et al 2015, Shimada et al 2016, Vander Zanden et al 2016, which, in some places, could be the result of adults and late-stage juveniles retaining high fidelity to known resources after drifting there as hatchlings (Hays et al 2010a. However, turtle behaviour is also more complex than previously hypothesized, with many exceptions to traditional life-history models.…”
Section: Q6 Where Are Key Foraging Habitats?mentioning
confidence: 99%